2021
DOI: 10.1055/a-1346-2899
|View full text |Cite
|
Sign up to set email alerts
|

Atrial Fibrillation in Patients with Embolic Stroke of Undetermined Source during 3 Years of Prolonged Monitoring with an Implantable Loop Recorder

Abstract: Background: Undocumented atrial fibrillation (AF) is suspected as a main stroke cause in patients with ESUS, but its prevalence is largely unknown. This prospective study therefore aimed at delineating the prevalence of AF in patients with ESUS using continuous cardiac monitoring by implantable loop recorder (ILR) with daily remote interrogation over a period of 3 years and its clinical consequences, including recurrent stroke. Methods: In consecutive patients with an ESUS diagnosis after complete work-up, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
27
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 29 publications
3
27
0
2
Order By: Relevance
“…6 While the overall risk of stroke was 2.5 higher in patients with SCAF, there was no clear temporal relationship between SCAF and the stroke event, i. e., only 8% of patients had SCAF within 30 days before stroke. 15 This seems similar to patients after ESUS as found in the current study 13 : none of the patients had SCAF in the 30 days before the stroke. Another subanalysis from the ASSERT trial informed that SCAF increases the risk only if one episode exceeds 24 hours.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…6 While the overall risk of stroke was 2.5 higher in patients with SCAF, there was no clear temporal relationship between SCAF and the stroke event, i. e., only 8% of patients had SCAF within 30 days before stroke. 15 This seems similar to patients after ESUS as found in the current study 13 : none of the patients had SCAF in the 30 days before the stroke. Another subanalysis from the ASSERT trial informed that SCAF increases the risk only if one episode exceeds 24 hours.…”
supporting
confidence: 87%
“…The role of SCAF in stroke patients is uncertain. 11,12 In this issue of Thrombosis and Haemostasis, Kitsiou et al report the 3-year follow-up data of a prospective observational study in 123 patients with ESUS, 13 which extends the initial findings published in 2017. 14 They report a cumulative SCAF prevalence of 41% and a stroke recurrence rate of 23%.…”
mentioning
confidence: 67%
“…In their review, Noubiap et al showed that higher rates of subclinical AF are identified in ESUS compared to CS (22% vs 14.2% at 6-months) [6] . This was confirmed in the recent study by Kitsiou et al who followed patients with ESUS for 3-years, finding 41% with subclinical AF and a much higher stroke recurrence of 23% [10] .…”
supporting
confidence: 62%
“…The role of SCAF in stroke patients is uncertain. 11,12 In this issue of Thrombosis and Haemostasis, Kitsiou et al report the 3-year follow-up data of a prospective observational study in 123 patients with ESUS, 13 which extends the initial findings published in 2017. 14 They report a cumulative SCAF prevalence of 41% and a stroke recurrence rate of 23%.…”
mentioning
confidence: 72%